Musik Gendang Lima Sendalanen Dulu Dan Sekarang Dalam Konteks Upacara Kematian - Obet Julpriadi Perangin Angin; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2022)
This study discusses the changes in the music of the Gendang Lima Sendalanen, and the role and function of the Gendang Lima Sendalanen itself in the death ceremony. This study aims to find out how Gendang Lima Sendalanen was and is now in the death ceremony. This type of research is qualitative research using qualitative descriptive methods. Data collection techniques were carried out using observation, interviews, documentation and literature study. Data analysis was carried out by collecting data, identifying, classifying, describing, analyzing and concluding the data. The results of this study indicate that there is a change in the presentation of the Sendalanen Five Drums which used to use five sandalwood drums, now uses a keyboard, which occurs and cannot be avoided in this modern era. Change does not change the culture itself because it is flexible, which changes only small things so that it does not change the culture.